Differentiation of Acidithiobacillus ferrooxidans and A-thiooxidans strains based on 16S-23S rDNA spacer polymorphism analysis - Bergamo, R. F.; Novo, MTM; Verissimo, R. V.; Paulino, L. C.; Stoppe, N. C.; Sato, MIZ; Manfio, G. P.; Prado, P. I.; Garcia, O.; Ottoboni, LMM (Elsevier B.V., 2004)
Restriction fragment length polymorphism (RFLP) and sequence analyses of the PCR-amplified 16S-23S rDNA intergenic spacer (ITS) were used for differentiating Acidithiobacillus thiooxidans strains from other related acidithiobacilli, including A. ferrooxidans and A. caldus. RFLP fingerprints obtained with AluI, DdeI, HaeIII, HinfI and MspI enabled the differentiation of all Acidithiobacillus reference strains into species groups. The A. thiooxidans strains investigated (metal mine isolates) yielded identical RFLP patterns to the A. thiooxidans type strain (ATCC 19377(T)), except for strain DAMS, which had a distinct pattern for all enzymes tested. Fourteen A. ferrooxidans mine strains were assigned to 3 RFLP groups, the majority of which were grouped with A. ferrooxidans ATCC 23270(T). The spacer region of one representative strain from each of the RFLP groups obtained was subjected to sequence analysis, in addition to eleven additional A. thiooxidans strains isolated from sediment and water samples, and A. caldus DSM 8584(T). The tRNA(IIe) and tRNA(Ala) genes, present in all strains analyzed, showed high sequence similarity. Phylogenetic analysis of the ITS sequences differentiated all three Acidithiobacillus species. Inter- and infraspecific genetic variations detected were mainly due to the size and sequence polymorphism of the ITS3 region. Mantel tests showed no significant correlation between ITS sequence similarity and the geographical origin of strains. The results showed that the 16S-23S rDNA spacer region is a useful target for the development of molecular-based methods aimed at the detection, rapid differentiation and identification of acidithiobacilli. (C) 2004 Elsevier SAS. All rights reserved.
Keywords: Acidithiobacillus ferrooxidans; Acidithiobacillus thiooxidans; 16S-23S rDNA spacer